Reactivity of free radical intermediates that form spontaneously during molecular chlorine action on acetylene and vinyl monomers at low temperatures: 9th International Conference on Cryocrystals and Quantum Crystals Odessa, Ukraine, September 2–8, 2012 (final part) - Gordon, D.A.; Volodina, V.A.; Mikhailov, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
In this study ESR, UV, VIS and IR spectroscopy, chromatography, calorimetry, and elemental analysis wereemployed to show the spontaneous formation of free radicals under low-temperature action of molecular chlorineon acetylene monomer p-diethynylbenzene, and vinyl monomer acrylamide. These radicals are able to initiate chain reaction of polymerization of monomers at low temperatures. This reaction results in a completely soluble polymer with a yield of 25 %, while an insoluble cross-linked polymer has been obtained during polymerization of p-diethynylbenzene initiated by other means. For example, under radiolysis by 1000 kGy the soluble fraction of obtained polymer was ≈ 1% while the overall yield was ≈ 10%. p-Diethynylbenzene polymerizes at temperatures close to chlorine melting (170 K). Polymerization of acrylamide takes place in the temperature range of 180–210 K with an yield of polymer ≈ 10%. The low-temperature chlorination of a 20%-solution of acrylamide in glycerol enables a twofold increase of the polymer yield, and a tenfold decrease of the chlorine content in it.